Role of calpastatin isoforms in breast cancer lymphovascular invasion - Sukkarn, Bhudsaban (2020)
Expression of calpastatin protein or exon3-containing variant (CASTexon3 mRNA) is negatively associated with various clinicopathological features of the high-risk group for breast cancer recurrence, including the presence of lymphatic invasion, a predominant form of lymphovascular invasion (LVI). It is mostly unknown how individual calpastatin isoforms originated from a single gene regulate such processes. This study, therefore, aimed to assess the role that individual calpastatin isoforms, encoded by CASTexon3 mRNA, play in regulating calpain activity as well as breast cancer progression and LVI in vitro.